Exploring the Determinants of Minimum Dietary Diversity in Infants and Toddlers: Insights from Pakistan’s Rural and Urban Populations - Ajaz, Misbah; Rizvi, Syeda Rida Kullsoom; Asif, Hafsa; Ghuman, Iqra Latif; Sahar, Tuba; Saeed, Anam; Alam, Farhad; Sajjad, Qamar (Indus Journal of Bioscience Research, 2025)
Determinants of Minimum Dietary Diversity (MDD) in infants and toddlers in rural and urban populations in Pakistan are explored in this study. MDD (consumption of foods from at least 4 food groups in 24 hours) is a marker of dietary quality and nutritional status. Selected rural and urban areas of Punjab were surveyed in a cross-sectional survey, including 600 infants and toddlers 5-20 months of age, and their primary caregivers. Structured surveys were used to collect data on dietary intake, socioeconomic factors, healthcare access, and food security. A total of 25% of children met the MDD criteria, with a significant difference of 48% in urban areas and 28% in rural areas (p < 0.001). Through multivariate logistic regression, it was found that several key determinants of MDD include maternal education (AOR: 2.4), household wealth (AOR: 3.1), market access (AOR: 2.7), healthcare utilization (AOR: 1.9), and food insecurity (AOR: 0.6). There were rural–urban disparities in maternal education and wealth as well as net access to markets. By contrast, rural children had less than half the consumption of fruits and protein-rich foods. The results suggest the importance of socioeconomic and infrastructural factors in explaining dietary diversity. Determinants of minimum dietary diversity (MDD) in Pakistan among infants and toddlers are examined in this study with emphasis on differences in these populations living in rural versus urban areas in Pakistan. Children living in urban areas have greater maternal education, wealth, and more access to healthcare and markets compared to children living in rural areas who suffer from food insecurity and socioeconomic challenges. Maternal education can be strengthened, market access increased, and structural inequalities addressed, contributing to increased dietary diversity and better nutrition and health outcomes for all children.